Notes on the Discovery of a Coped Monument and an Incised Cross-slab at the Graveyard, St Boniface Church, Papa Westray, Orkney (Proceedings of the Society of Antiquaries of Scotland, 1921)
The coped stone has sloping sides covered with three rows of well-defined tiles, or shield-shaped scale-like ornamentation. Along the ridge, which is flat, there is a deeply-cut channel. The stone, which is of red freestone much covered with lichen,\r lies due east and west, the broader end to the west. The cross-slab was found while a grave was being dug. Incised on the face is a geometrical four armed cross within a circle, the diameter of which is 10 inches. This cross is surmounted by a small equal-armed cross, the top arm being imperfect. It has a single step at the foot, and to this extent it resembles a Calvary cross. Each end of the side arms terminates in a crescent, a very unusual occurrence.